MATHEMATICS LEARNING BASED ON BATIK PANDEGLANG ETNOMATICS TOWARDS GEOMETRY TRANSFORMATION LEARNING MATERIALS - Ida Ida (Universitas Tanjungpura, 2023)
Mathematics as a branch of science that cannot be separated from its existence in everyday life. The existence of mathematics as a science is timeless. The concept of mathematics is contained in the culture that develops in society. The mathematical concepts contained in this culture are called ethnomathematics. Ethnomathematics is a link between culture, mathematics, and education. The purpose of this study was to determine the practice of ethnomathematics in the manufacture of Pandeglang batik and the integration of Pandeglang batik as a learning resource for high school geometry transformation mathematics. This study uses qualitative research with an ethnographic approach. The instrument in this study is the researcher himself and cannot be replaced by someone else. Data collection was done by interview, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study are basic mathematical activities carried out when making batik pandeglang and mathematical concepts contained in the batik pandeglang motif such as translation, reflection, rotation and dilation. Batik motifs that contain mathematical concepts are integrated into high school mathematics problems so that they can become new sources of learning that are more interesting